2020
DOI: 10.1016/j.bone.2020.115446
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thinning and accumulation of large cortical pores in the tibia reflect local structural deterioration of the femoral neck

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…2a). The estimations of tissue impedance and structural parameters from SAM images has been described in detail in previous studies [30,35,37]. Briefly, the bone matrix was segmented from the background using an adaptive threshold [38].…”
Section: Image Registration and Microstructure Parameter Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…2a). The estimations of tissue impedance and structural parameters from SAM images has been described in detail in previous studies [30,35,37]. Briefly, the bone matrix was segmented from the background using an adaptive threshold [38].…”
Section: Image Registration and Microstructure Parameter Extractionmentioning
confidence: 99%
“…To our knowledge, this is the first non-ionizing method that can assess independently and noninvasively tissue impedance, pore density and characteristic features of the pore size distribution. The prevalence of large cortical pores and cortical thinning in the tibia have been shown to reflect a compromised femoral neck structure and reduced femur strength [1,37]. Except for the ultimate force under sideway fall conditions, the prediction accuracy of mechanical properties of the proximal femur was better using Ct.Th and backscatter parameters than that of areal bone mineral density.…”
Section: A Cortical Bone Backscatter Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…( 14 ) Postmenopausal women with osteopenia have higher cortical porosity and thinner cortices at the distal radius and tibia than women with normal aBMD. ( 15 ) In an ex vivo study, cortical thinning and the prevalence of large BMUs in the tibia were found to be associated with structural deterioration of the femoral neck ( 16 ) and proximal femur strength. ( 17 ) Although cortical porosity of the tibia was not associated with femoral stiffness or strength, the proportion of Ct.Po attributable to large pores (diameter >100 μm) was significantly associated with hip strength in both standing ( r = −0.61) and falling ( r = 0.48) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the femoral neck of elderly people (age between 60 and 90 years), decreases of cortical thickness (Ct.Th) and porosity (Ct.Po) by ~4 % and ~32 %, respectively, per decade with no significant changes in pore density (Ct.Po.Dn) have been reported 15 . Decreased cortical thickness and the prevalence of large BMU's have been shown to reduce bone strength 16 and structural deterioration 17 . In contrast, cortical thinning is partially compensated by the apposition of new tissue matrix at the periosteal interface leading to an increased bone diameter and a further increase of the pore diameter gradient in the radial bone direction.…”
Section: Introductionmentioning
confidence: 99%